Histomorphology of Testes in Cattle Egret (Bubulcus ibis) - Nidhi Gupta, (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on male cattle egret (Bubulcus ibis). After dissection of the bird, thetopography of testes was recorded and then fixed in 10% neutral buffered formalin. Sections of 4-6 µm inthickness were obtained and stained with Harris heamatoxylin and Eosin stain (H&E), Van Gieson's andSchmorl's method. The left testis was placed slight cranially than the right one and was larger in size. Thethickness of capsule ranged between 22.80- 28.40 µm. The capsule was made up of dense connective tissue andorganised into three layers of tissue, namely outer tunica serosa, the middle and thickest layer, the tunicaalbuginea, and the poorly differentiated inner tunica vasculosa. Convoluted seminiferous tubules were lined by astratified epithelium of spermatogenic cells and Sertoli cells. The height of epithelium rangedbetween 14.64-20.40 µm. Diameter of seminiferous tubules rangedbetween 46.6- 56.50 µm. There was presence of melanin inthe interstitium and capsule which correlated with black color appearance of testes macroscopically.